A novel and rapid LC-MS/MS assay method for the determination of canagliflozin in human plasma by solid phase extraction technique and its application to a pharmacokinetic study - Somarouthu Venkata Saibaba; Nageswara Rao Pilli; Bhavani Prasanna Kumar Bimireddy; Pitchaimuthu Shanmuga Pandiyan (SpringerOpen, 2018)
Objective: The aim of the present study was to develop and validate a simple LC-MS/MS for the determination of canagliflozin in human plasma. The proposed method is fully validated for the precision, accuracy and various stability tests. Methods: The linearity of the method was established in the concentration range 10.3-6019 ng/mL with r2 ≥ 0.99. Solid-phase extraction (SPE) technique was used for the extraction of canagliflozin and canagliflozin d4 as internal standard (IS). The clean samples injected into LC-MS/MS system set with turbo ion spray (TIS) source and operated in multiple reaction monitoring (MRM) mode. Results: Precision and accuracy of the method was determined using five analytical batches and results were meeting as per the recent US FDA guidelines. Also, a variety of stability tests were executed in plasma samples and in neat samples are comply recent bioanalytical guidelines. The total run time was 2.5 min to analyze canagliflozin and the IS, thus can analyze more than 300 samples in a day. Conclusion: The proposed LC-MS/MS method is novel, sensitive and rapid for the quantitative determination of canagliflozin in human plasma. The method describes the complete method development and validation process and is well suitable for pharmacokinetic or bioavailability/bioequivalence application. Keywords: Canagliflozin, LC-MS/MS, Solid-phase extraction (SPE), Method validation, Pharmacokinetics